Factors Affecting Glycemic Control in Diabetes Mellitus Patients - Wireno, Eros Hanif; Setiawan, Andreas Arie; Hendrianingtiyas, Meita; Pramudo, Setyo Gundi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Indonesia ranked seventh in the prevalence of diabetes mellitus in the world. Improved glycemic control has been proven to prevent the diabetes and its complications. Adherence to treatment, weight regulation with benchmarks for Body Mass Index (BMI) indicators, activity or exercise habits, diet, and smoking history play an important role in glycemic control. Objective: The aim  of  this study was to identify factors affecting glycemic control in outpatient with diabetes mellitus.Methods: A cross sectional study  among 32 diabetes mellitus patients.This study was conducted from April 2019 to September 2019 at Rumah Sakit Nasional Diponegoro (RSND), Semarang. The glycemic control status were assesed by HbA1c. Factors such medication adherence, diet adherence, smoking status, and physical activity were assesed with a structured questionnaire. Anthropometric measurement done to get the BMI status. Data were analyzed with bivariat analysis with chi square test (p<0.05).Result: The factors that were significantly have relationship with glycemic control status are diet adherence (p=0.046), and medication adherence (p=0.040). Physical activity, smoking status and BMI doesn’t have significant relationship with glycemic control status.Conclusion: Factors affecting glycemic control of diabetes mellitus patients in this study were diet adherence and medication adherence. History of smoking, BMI, and physical activity were not factors that influenced the control status in diabetes mellitus patients in this study.